The vascular endothelium as decision maker in lung injury - Klein, Diana (Frontiers in Cell and Developmental Biology, 2025)
The vascular endothelium is the largest organ in the human body, capable of performing a wide range of cellular signaling and synthetic functions. It is also subjected to considerable mechanical stress due to the shear forces generated by blood flow, which amounts to approximately 10,000 L per day. The endothelial layer plays a crucial role in regulating vascular tone locally and controlling the extravasation of certain blood components. Additionally, it is integral to the coagulation process. The endothelium serves as the entry point for immune cells, which migrate from the bloodstream to surrounding tissues by passing through the endothelial layer. This underscores the importance of proper endothelial function for the health of the body’s tissues and organs. When the endothelium fails to perform these functions adequately, leading to endothelial dysfunction, pathological conditions are more likely to develop. Notably, acute lung injury and its severe form, acute respiratory distress syndrome (ARDS), are often associated with endothelial dysfunction. ARDS refers to pulmonary edema with increased vascular permeability resulting from various pulmonary or systemic insults. In most cases, an exaggerated inflammatory and pro-thrombotic response to the initial insult causes disruption of the alveolar–capillary membrane and leakage of vascular fluid. This review emphasizes the central role of the vascular endothelium in acute conditions and seeks to clarify the concepts and interplay between endothelial activation, dysfunction, and damage.